NLO QCD+NLO EW corrections to diboson production matched to parton shower - Mauro Chiesa; Carlo Oleari; Emanuele Re (European Physical Journal C: Particles and Fields, 2020)
Abstract We present the matching of NLO QCD and NLO EW corrections to parton showers for vector-boson pair production at the LHC. We consider leptonic final states, including resonant and non-resonant diagrams, spin correlations and off-shell effects. Our results are obtained interfacing the Recola2-Collier one-loop provider with the POWHEG-BOX-RES framework. We discuss our implementation, we validate it at fixed order, and we show our final results matched to parton shower. A by-product of our work is also a general interface between Recola2-Collier and POWHEG-BOX-RES. This is the first time that EW and QCD corrections to diboson production are consistently matched to parton showers.